1965
DOI: 10.1113/expphysiol.1965.sp001778
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effect of Vasopressin Upon the Composition of the Rat Renal Cortex and Medulla

Abstract: Rats in water diuresis were given intravenous injections of vasopressin, or of isotonic NaCl for controls. Serial urine sampling showed that maximal osmolality and minimal flow were achieved half an hour after vasopressin injection, and that urea excretion was low at this time. In animals killed half an hour after injection, the composition of the renal papilla, medulla and cortex was studied.The urea and ammonium concentration and content increased in the inner medulla after vasopressin injection, and the wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1965
1965
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…In contrast, Jaenike has pre-sented indirect evidence suggesting that vasopressin does not enhance the medullary sequestration of nonurea solute (3). Although other investigators have reported similar studies (4,5), there still is no agreement whether or not vasopressin promotes the medullary sequestration of sodium. The availability of rats with a genetic, apparently absolute, defect for synthesizing vasopressin (6) seemed to present an ideal opportunity for reinvestigating this problem.…”
mentioning
confidence: 61%
“…In contrast, Jaenike has pre-sented indirect evidence suggesting that vasopressin does not enhance the medullary sequestration of nonurea solute (3). Although other investigators have reported similar studies (4,5), there still is no agreement whether or not vasopressin promotes the medullary sequestration of sodium. The availability of rats with a genetic, apparently absolute, defect for synthesizing vasopressin (6) seemed to present an ideal opportunity for reinvestigating this problem.…”
mentioning
confidence: 61%
“…Ten rats and three hamsters were studied during water diuresis induced by intraperitoneal distilled water (4 ml./100 g. body weight, injected under light ether anaesthesia). G. A. Bray [personal communication] found this to produce a more prolonged water diuresis than did intragastric water, and his findings have been confirmed [Saikia, 1965]. The hamsters and five of the rats had access to tap water and cabbage leaves, and the other five rats were deprived of food and water for 24 hr.…”
mentioning
confidence: 69%
“…Whatever the mechanisms whereby sodium accumulation is maintained in the medulla, they still operate during water diuresis, whereas the urea accumulation is largely dispersed. How far vasopressin can reverse these changes will be considered in the subsequent paper [Saikia, 1965].…”
Section: Amrnmoniummentioning
confidence: 99%
“…Each of the natural GCs: Arg, GAA, guanidinosuccinic acid (GSA), CT, creatinine (CTN), homoarginine (HArg), α-N-acetylarginine (α-N-AA), β-guanidinopropionic acid (β-GPA), γ-guanidinobutyric acid (γ-GBA), α-keto-δ-guanidinovaleric acid (α-keto-δ-GVA), guanidine (G) and methylguanidine (MG) exhibit typical distribution patterns along the cortico-papillary axis [16]. Moreover, it is noteworthy that, in adult rats, the tissue concentrations of α-keto-δ-GVA, GSA, CTN, MG, α-N-AA and γ-GBA increase steeply from the inner stripe of the outer medulla to the papillary tip and, thus, constitute gradients which run in parallel to the well-known urea and osmotic gradients [26,31]. These latter two gradients are known to change in response to antidiuresis and diuresis and changes in medullary osmolality are accompanied by corresponding variations in the intracellular concentrations of organic osmolytes.…”
Section: Introductionmentioning
confidence: 93%